2011
DOI: 10.1192/bjp.bp.110.081513
|View full text |Cite
|
Sign up to set email alerts
|

Rapid acute treatment of agitation in individuals with schizophrenia: multicentre, randomised, placebo-controlled study of inhaled loxapine

Abstract: BackgroundThere is a need for a rapid-acting, non-injection, acute treatment for agitation.AimsTo evaluate inhaled loxapine for acute treatment of agitation in schizophrenia.MethodThis phase III, randomised, double-blind, placebo-controlled, parallel-group study (ClinicalTrials.gov number NCT00628589) enrolled 344 individuals who received one, two or three doses of inhaled loxapine (5 or 10 mg) or a placebo. Lorazepam rescue was permitted after dose two. The primary efficacy end-point was change from baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
98
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 24 publications
(25 reference statements)
5
98
0
9
Order By: Relevance
“…The intramuscular form of loxapine is no longer marketed in the United States, but is frequently used in France for the acute treatment of agitation. 13 Intramuscular antipsychotics have a T max of 90 minutes and can take up to 60 minutes to reduce agitation, [14][15][16][17] and symptoms can escalate during this period. Moreover, intramuscular administration is often resisted by patients.…”
mentioning
confidence: 99%
“…The intramuscular form of loxapine is no longer marketed in the United States, but is frequently used in France for the acute treatment of agitation. 13 Intramuscular antipsychotics have a T max of 90 minutes and can take up to 60 minutes to reduce agitation, [14][15][16][17] and symptoms can escalate during this period. Moreover, intramuscular administration is often resisted by patients.…”
mentioning
confidence: 99%
“…Some independent variables might influence this result, including the inherent differences in the studies concerning the cohort size, population characteristics, and evaluation of adverse events. In the study of Lesem et al (2011), some patients were smokers (a comorbidity), and the clinical trial population included Hispanic and Asian minorities; these characteristics differ from those in a study by . Relatively few adverse events were reported, which were mild, subjective and typical (headache and dysgeusia), and the presence of heterogeneity is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of two studies (Allen et al, 2011; Lesem et al, 2011) demonstrated potential evidence for the superiority of LOXi compared to a placebo regardless of the dosage for the treatment of chronic schizophrenic patients for agitation. The initial effects were observed 10 minutes after inhalation, and the intervention was more effective than the placebo for 2 hours following the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, following inhalation of loxapine, the median T max was 2 minutes. Phase II [50] and Phase III [51] studies in patients with schizophrenia or schizoaffective disorder demonstrated that inhaled loxapine (5 mg and 10 mg doses) was well tolerated and had dose-dependent anti-agitation effects without evidence of excessive sedation. The superior anti-agitation effects of inhaled loxapine compared with placebo were evident at 10 minutes after administration, and this early onset of action appears to be the most rapid anti-agitation effect ever reported in placebocontrolled trials [51].…”
Section: ) Inhalable Loxapinementioning
confidence: 99%